ANALISIS DAMPAK BUDAYA PEMBANGUNAN BANDARA INTERNASIONAL TERHADAP MASYARAKAT SEKITARNTYA - Windia, Wayan; Suamba, Ketut; Sudarta, Wayan; Adikampana, Made (Program Studi Agribisnis Fakultas Pertanian Universitas Dwijendra, 2011)
Cultural impact in international airport development for the surrounding community is very important to be analyzed. Those analyzation very useful for the new airport development, because we can anticipate the positive and negative impact of the international airport development. As for the result of the positive and negative impact of Ngurah Rai International Airport development are catagorizied into aspect of values (thinking pattern), social, and artifact.